Monitoramento das propriedades térmicas das borrachas naturais de novos clones: IAC 301 e IAC 303 - Moreno, Rogério M. B.; Martins, Maria Alice; Mattoso, Luiz H. C.; Corradini, Elisângela; Job, Aldo E. [UNESP]; Gonçalves, Paulo De S. (Associação Brasileira de Polímeros, 2013)
A borracha natural (BN) de três clones de seringueira [Hevea brasiliensis (Willd. exAdr. de Juss. Muell.-Arg.)] de um período de sete meses foi obtida por coagulação do látex com solução de ácido acético a 10% e seca a 65°C. As curvas TG-DTG foram utilizadas para monitorar as propriedades térmicas da BN. Os resultados indicaram pequenas variações entre clones e coletas, exceto no valor de Tf-T0, indicando que o clone IAC 301 sofre degradação mais rápida durante o processo termo degradação da BN seca. Não houve diferenças significativas nos valores de Tg entre clones e coletas.

Natural rubber (NR) tapped from three clones of the rubber tree [Heveabrasiliensis (Willd. ex Adr. de Juss. Muell.-Arg.)] over a seven month period was obtained by coagulation of lattices with 10% acid acetic and dried at 65 °C. TG-DTG curves were used to monitor thermal properties of NR. The TG-DTG results indicated very small differences among the clones and tappings, except in the value of Tf-T0, which indicated that the IAC 301 clone suffered the fastest thermal degradation, during decomposition of the dried, raw NR. There was no significant difference in Tg values among clones and tappings.
Monitoring the thermal properties of natural rubbers from new clones: IAC 301 and IAC 303
Keywords: Borracha natural crua; novos clones; monitoramento; propriedades térmicas; Raw natural rubber; new clones; monitoring; thermal properties